The Effect of the Day of The Week Effect on the Stock Return of Companies in the Banking Industry Sector on the Indonesia Stock Exchange for the 2022 Period - Desmizar, Desmizar (Baca Dulu Publisher, 2024)
This research purposes for determining the effect of the Day of The Week Effect on Stock Returns in the Banking Industry Sector Companies on the Indonesia Stock Exchange for the 2022 Period. The variables examined in this study were the Day of the Week Effect and the Stock Return. The population in this study were 43 companies in the banking industry sector listed on the Indonesia Stock Exchange for the period 2022. The sample used in this study were 33 companies with a purposive sampling method. This research uses descriptive statistics and multiple linear regression analysis processed with SPSS 23. The results of this study indicate that the variable day of the week effect on Monday and Wednesday has a significant effect on stock returns. The results of this study also indicate that the day of the week effect variable simultaneously affects stock returns.